Sharing capacity on the Climate, Peace, and Resilience Nexus among civil society organizations in MENA - Rabie, Sara; Jaskolski, Martina; Taiwo, Ibukun (CGIAR, 2025)
The blogpost reports on a capacity sharing event on the climate, peace, and resilience nexus for civil society organizations in the MENA region.